THE EFFECT OF EXPERIENTIAL MARKETING ON WORD OF MOUTH WITH CUSTOMER SATISFACTION AS A MEDIATION VARIABLE (CASE STUDY AT SRIVIJAVA COFFEE) - Aditya Liliyan; Fahmi Rizka Luqmana (Program Studi Magister Manajemen Universitas Advent Indonesia, 2025)
This study aims to analyze the effect of experiential marketing on word of mouth, with customer satisfaction as a mediating variable, in the context of Srivijava Coffee consumers. The research is based on the importance of customer experience in shaping satisfaction and encouraging positive communication behavior among consumers. A quantitative research method was employed using Structural Equation Modeling (SEM), with primary data collected through questionnaires distributed to 100 respondents. Data analysis was conducted using R software with the Maximum Likelihood estimation method. The results show that experiential marketing has a positive and significant effect on customer satisfaction, with a standardized estimate value of 0.738. Furthermore, customer satisfaction significantly influences word of mouth (0.349), and experiential marketing also has a direct impact on word of mouth (0.464). These findings indicate that customer satisfaction partially mediates the relationship between experiential marketing and word of mouth. The R-squared values of 0.544 for customer satisfaction and 0.576 for word of mouth demonstrate that the model has a strong explanatory power for the dependent variables. The model fit indices also indicate a good fit, with CFI = 0.973, TLI = 0.969, RMSEA = 0.046, and SRMR = 0.044. The study concludes that enhancing customer experience significantly increases satisfaction, which in turn encourages customers to recommend Srivijava Coffee to others. Therefore, it is recommended that management continues to strengthen high-impact aspects of experiential marketing, such as service quality, store atmosphere, and emotional interaction with customers.